2013
DOI: 10.1089/jpm.2013.0100
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Agitation Severity of Hyperactive Delirium in Terminally Ill Cancer Patients in a General Hospital Using Ordered Logistic Regression Analysis

Abstract: Our study indicates that male sex, T-bil, antibiotic therapy, NSAID therapy, and hematological malignancy are significant predictors for agitation severity of hyperactive delirium in terminally ill cancer patients in a general hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…3,11,16 However, several studies demonstrated that item 9 is associated with the neurobehavioral dimension and severity of agitation, and they used it as an outcome variable to assess hyperactive delirium in terminally ill cancer patients. [13][14][15] Although this limitation was unlikely to have a significant impact on the results of our study, the validity and reliability need to be assessed between the total MDAS score and item 9 of the MDAS.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…3,11,16 However, several studies demonstrated that item 9 is associated with the neurobehavioral dimension and severity of agitation, and they used it as an outcome variable to assess hyperactive delirium in terminally ill cancer patients. [13][14][15] Although this limitation was unlikely to have a significant impact on the results of our study, the validity and reliability need to be assessed between the total MDAS score and item 9 of the MDAS.…”
Section: Discussionmentioning
confidence: 93%
“…14 The rationale for adopting item 9 of the MDAS as an outcome measurement instead of the total MDAS score was that several studies demonstrated that item 9 can distinguish the severity of agitation, and thus be used as an outcome variable to assess hyperactive delirium in terminally ill cancer patients. [13][14][15] The physicians coded item 9 with "hyperactive features" or "mixed features" based on the last few hours of observations. We assessed the presence of agitated delirium on admission and at 3 days before death.…”
Section: Measurementsmentioning
confidence: 99%
See 3 more Smart Citations